Occupational Therapy Based Interventions: For Supporting Physically Disabled Students who are Bullied. - Panchal, Prerna; Ali, Nazia (International Journal of Psychosocial Rehabilitation, 2022)
Bullying is considered as a serious problem and is the most frequently observed antisocial behavior among adolescents and children. The purpose of this study was to determine effectiveness of occupational therapy-based interventions for supporting physically disabled students who are bullied.Method- This was a Pretest-Posttest, Experimental, Prospective, Single center study in which 30 participants were selected from an inclusive school in Delhi, India. Children with disability were recruited with Age of 11 to 16 years, Regular school going children (both boys and girls) who were willing to participate and able to follow study instructions (The average or normal, range of IQ of 90 to110 examination) also, who have higher score in Multidimensional Peer Victimization Scale were included in the study.Results - Bullying was assessed among children using the Multidimensional peer victimization scale. Children were re-assessed after the implementation of intervention and Data thus collected was statistically analyzed. The pre-and post-test scores provide evidence that there is decrease in scores of multi-dimensional peer victimization scale.